Hydroformylation of 1-octene using rhodium–phosphite catalyst in a thermomorphic solvent system - Shaharun, Maizatul Shima (Elsevier, 2009)
The use of a liquid–liquid biphasic thermomorphic or temperature-dependent multicomponent solvent (TMS) system,in which the catalyst accumulates in one of the liquid phases and the product goes preferably to the other liquid phase,can be an enabling strategy of commercial hydroformylation processes with high selectivity, efficiency and ease of product separation and catalyst recovery. This paper describes the synthesis of n-nonanal, a commercially important fine chemical,by the hydroformylation reaction of 1-octene using a homogeneous catalyst consisting of HRh(PPh3)3(CO) andP(OPh)3 in a TMS-system consisting of propylene carbonate(PC),dodecane and 1,4-dioxane. At a reaction temperature of 363K, syngas pressure of 1.5 MPa and 0.68mM concentration of the catalyst,HRh(CO)(PPh3)3, the conversion of 1-octene and the yield of total aldehyde were 97%and 95%,respectively.With a reaction time of 2h and a selectivity of 89.3%,this catalytic system can be considered as highly reactive and selective compared to conventional ones.The resulting total turnover number was 600,while the turnover frequency was 400 h−1. The effects of increasing the concentration of 1-octene,catalyst loading,partial pressure of CO and H2 and temperature on the rate of reaction have been studied at 353,363 and 373K. The rate was found to be first order with respect to concentrations of the catalyst and 1-octene, and the partial pressure of H2. The dependence of the reaction rate on the partial pressure of CO showed typical substrate inhibited kinetics. The kinetic behavior differs significantly from the kinetics of conventional systems employing HRh(CO)(PPh3)3 in organic solvents. Most notable are the lack of olefin inhibition and the absence of a critical catalyst concentration. A mechanistic rate equation has been proposed and the kinetic parameters evaluated with an average error of 5.5%. The activation energy was found to be 69.8kJ/mol.